PERANAN PEMERINTAH DAERAH DALAM MEMFASILITASI KETENAGAKERJAAN UNTUK MENINGKATKAN INVESTASI PUBLIK DI KABUPATEN MELAWI, PROVINSI KALIMANTAN BARAT - P. R. Benirobin; Muchlis Hamdi; Rossy Lambelanova; Reydonnizar Moenek (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
The research objective is to obtain a picture of the sub-optimal role of the Melawi Regency Government in facilitating employment to increase public investment in Melawi Regency. The research method is qualitative with interviews, observation and documentation. The researcher conducted an analysis guided by the scope of facilitating manpower contained in Law Number 13 of 2003, namely facilitating job training, facilitating employment placement and expanding job opportunities and facilitating industrial relations; and using Siagian's role theory which states that the role of government is as a stabilizer, innovator, modernizer, pioneer and implementer.